METHODOLOGY OF TEACHING CONSCIOUS, FAST, FLUENT READING AND COMPREHENSION OF THE TEXT IN PRIMARY CLASS STUDENTS (Conferencea, 2024)
The article analyzes methodical approaches aimed at forming conscious, fast and fluent reading skills in elementary school students. In order to increase the reading speed of the students and develop the ability to understand the text in depth, the study was organized on the basis of phonetic analysis, exercises to increase the reading speed, and the use of neuropedagogical technologies. It was found that each of these approaches serves to improve the cognitive abilities of students and more effective learning of educational materials.